The use of two different MLPA kits in 22q11.2 Deletion Syndrome - Evers, L.J.M. (Eur J Med Genet, 2016)
22q11.2 deletion syndrome (22q11DS) is one of the most common recurrent copy-number variant disorder, caused by a microdeletion in chromosome band 22q11.2 and occurring with a population prevalence of 1 in 2000. Until today there has been no evidence that the size of the deletion has an influence on the clinical phenotype. Most studies report that 22q11DS is associated with mild or borderline intellectual disability. There are a limited number of reports on 22q11DS subjects with moderate or severe intellectual disability. In this study we describe 63 adult patients with 22q11DS, including 22q11DS patients functioning at a moderate to severe intellectual disabled level. Deletion size was established with an experimental Multiplex ligation-dependent probe amplification (MLPA) mixture (P324) in addition to the commonly used MLPA kit (P250). We compared deletion size with intellectual functioning and presence of psychotic symptoms during life. The use of the experimental MLPA kit gives extra information on deletion size, only when combined with the common MLPA kit. We were able to detect eleven atypical deletions and in two cases the deletion size was shorter than all other “typical ones”. We conclude that the use of the experimental kit P324 gives extra information about the deletion size, but only when used together with the standard P250 kit. We did not found any relation of deletion size with intelligence or presence of psychosis.